STRATEGI KOMUNIKASI DAKWAH BANG KEVIN MELALUI MEDIA TIKTOK - Ilman Zuhar Alan Kiffani; Ahmad Fakhruddin Fajrul Islam (Universitas Hasyim Asy'ari, 2023)
This article describes the important role of da'wah in technological developments in the millennial era. Bang Kevin is a Tiktok account that is in the da'wah category, this can be concluded because there are many videos containing da'wah messages packaged in millennial and interesting language, so that most other Tiktok users can understand and accept them, namely young people to adults. This study aims to find out how Kevin Kausar's universal da'wah strategies and techniques are in Bang Kevin's TikTok account. This study uses a qualitative approach while the method used by researchers is descriptive analysis